The use code experts and code mixers in the classroom learning process - Serungke, Mayang (Institute of Education and Social Research, 2024)
The use of language in teaching and learning interactions must basically use language that is clear and can be understood by students. Each lecturer has different views on the use of language in learning interactions. If in a speech event there is a transition from a clause of a language to a clause of another language, then the event that occurs is code switching. But if in a speech event, what is used consists of mixed clauses and phrases (hybrid clauses, hybrid phrases), then the event that occurs is code-mixing. This research method uses a descriptive qualitative approach because the data is presented in the form of words (descriptions) systematically, facts. The data collection technique in this research uses the listening method, along with its advanced techniques, namely tapping techniques, free listening techniques (SBLC), recording techniques and recording techniques. Based on the results found in the learning process at UIN North Sumatra, Medan, especially the Tadris Indonesian Language Study Program in semester VI. During five days between April 22-26, 2023. Three code-switching utterances and three code-mixing utterances were found.